2019
DOI: 10.1097/md.0000000000014556
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in patients with advanced extrahepatic cholangiocarcinoma

Abstract: Extrahepatic cholangiocarcinoma (ECC) is an aggressive malignancy causing a lot of fatalities and comorbidities. Endoscopic biliary stenting (EBS) is mostly needed for ECC. In this study, we aimed to investigate the prognostic factors for the overall survival (OS) and the factors predicting the patients eligible for chemotherapy after EBS in ECC. We retrospectively screened 153 advanced ECC patients who underwent EBS for jaundice to make the patients eligible for chemotherapy. Patient's clinical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…We identified a number of factors that were associated with decreased OS after propensity score weighting and doubly robust estimation. The majority of these, such as Charlson scores of 1 or higher, positive LVSI, positive margins, lymph node positivity, tumors larger than 2 cm, age > 65, high-grade disease, and node positivity, are consistent with previously known prognostic factors in CCA [ 2 , 33 , 34 ]. Perhaps surprisingly, there was not an association of treatment modality with overall survival; however, this may be a result of insufficient power to detect a difference with only a small number of patients treated with radiation therapy alone.…”
Section: Discussionsupporting
confidence: 79%
“…We identified a number of factors that were associated with decreased OS after propensity score weighting and doubly robust estimation. The majority of these, such as Charlson scores of 1 or higher, positive LVSI, positive margins, lymph node positivity, tumors larger than 2 cm, age > 65, high-grade disease, and node positivity, are consistent with previously known prognostic factors in CCA [ 2 , 33 , 34 ]. Perhaps surprisingly, there was not an association of treatment modality with overall survival; however, this may be a result of insufficient power to detect a difference with only a small number of patients treated with radiation therapy alone.…”
Section: Discussionsupporting
confidence: 79%
“…The majority of these, such as Charlson scores of 1 or higher, positive LVSI, positive margins, lymph node positivity, tumors larger than 2 cm, age > 65, high grade disease, and node positivity are consistent with previously known prognostic factors in CCA. 2,33,34 An important novel nding of our study is the nding that delays in initiation beyond the median time point of 59 days were associated with decrements in OS. While this has not been previously described in CCA, there are a number of malignancies in which delay to adjuvant therapy has been shown to be associated with worse outcomes.…”
Section: Discussionmentioning
confidence: 77%
“…30 Transaminases have been reported to be associated with the development of hepatocellular cancer, intrahepatic and extrahepatic cholangiocarcinoma. [31][32][33] Epidemiological studies have examined the association of ALT with the risk of prostate cancer, but the findings have been conflicting. For example, a case-cohort study found that ALT levels were not associated with the risk of prostate cancer (hazard ratio (HR): 0.89, 95% CI: 0.73-1.07, P=0.212).…”
Section: Discussionmentioning
confidence: 99%